KARAKTERISTIK ASMA PADA ANAK DI PUSKESMAS I DENPASAR TIMUR TAHUN 2019-2021 - Made Michel Kresnayasa; I Nyoman Budi Hartawan; I Gusti Lanang Sidiartha; Dyah Kanya Wati (Universitas Udayana, 2021)
Asthma is a chronic inflammatory disease that occurs in the respiratory tract and most commonly seen in children. The prevalence of asthma continues to increase from time to time, according to WHO and GINA, the number of people with asthma in the world reaches 300 million people, this figure is expected to continue to increase to 400 million people in 2025. This study aims to determine the characteristics of children with asthma in puskesmas I East Denpasar, 2019 - 2021. This research was a descriptive study by taking data of medical records from 2019 to 2021 at Puskesmas I East Denpasar. The sample used is a child patient diagnosed with asthma with a total sampling method, that means the whole population is the subject of the study. The results of taking medical record data of 74 samples showed that cases of asthma in children at Puskesmas I East Denpasar in 2019-2021 were more common in males than females and were dominated by children with an age range of 0-4 years. In addition, asthma patients in children were mostly found in children with excess nutritional status without a history of atopic dermatitis. Asthma sufferers in children are mostly found in males and in the age group of 0 - 4 years. The majority of children who suffer from asthma are children with excess nutritional status and only a few have a history of atopic dermatitis. Keywords: Asthma, characteristics, children, nutritional status.